2017
DOI: 10.3390/ma10010033
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical, In Vitro, and In Vivo Evaluation of a 3D Unidirectional Porous Hydroxyapatite Scaffold for Bone Regeneration

Abstract: Abstract:The unidirectional porous hydroxyapatite HAp (UDPHAp) is a scaffold with continuous communicated pore structure in the axial direction. We evaluated and compared the ability of the UDPHAp as a three-dimensional (3D) bone tissue engineering scaffold to the interconnected calcium porous HAp ceramic (IP-CHA). To achieve this, we evaluated in vitro the compressive strength, controlled rhBMP-2 release behavior, adherent cell morphology, cell adhesion manner, and cell attachment of UDPHAp. As a further in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 28 publications
(41 reference statements)
2
25
0
Order By: Relevance
“…First, we evaluated the engraftment and diff erentiation capacity of iPS-NCLC-MSCs on HA, the major mineral component of bone, and demonstrated that they exhibited the typical morphology of MSCs and could differentiate into osteoblasts by osteogenic induction. These results coincided with a previous study showing that MC3T3-E1 cells grew well on the UDPHAp surface 20) and suggested that iPS-NCLC-MSCs could maintain the differentiation capacity into osteoblasts on HA when transplanted. Second, we transplanted iPS-NCLC-MSCs with β-TCP in a calvarial defect and showed that the cells contributed to bone regeneration with no formation of tumor in vivo.…”
Section: Gfp Osx Mergesupporting
confidence: 80%
See 1 more Smart Citation
“…First, we evaluated the engraftment and diff erentiation capacity of iPS-NCLC-MSCs on HA, the major mineral component of bone, and demonstrated that they exhibited the typical morphology of MSCs and could differentiate into osteoblasts by osteogenic induction. These results coincided with a previous study showing that MC3T3-E1 cells grew well on the UDPHAp surface 20) and suggested that iPS-NCLC-MSCs could maintain the differentiation capacity into osteoblasts on HA when transplanted. Second, we transplanted iPS-NCLC-MSCs with β-TCP in a calvarial defect and showed that the cells contributed to bone regeneration with no formation of tumor in vivo.…”
Section: Gfp Osx Mergesupporting
confidence: 80%
“…After checking the expression of NC marker as previously described 12) , iPS-NCLCs were cultured and maintained in DMEM containing 10% FBS and 50 U/ml and 50 µg/ml PenicillinStreptomycin on CorningTM PrimariaTM tissue culture dishes (Thermo Fisher Scientifi c) to induce MSCs. For iPS-NCLC-MSCs cultured on hydroxyapatite (HA), unidirectional porous HA scaffolds [18][19][20] (Kurarife, Kuraray Medical Inc., Tokyo, Japan) were coated with fi bronectin overnight at 4°C and washed with PBS 3 times. Dissociated iPS-NCLC-MSCs were seeded on the HA scaff olds and cultured in DMEM supplemented with 10% FBS for 2 days before osteoinduction.…”
Section: Cell Culture and Msc Inductionmentioning
confidence: 99%
“…Recent studies have reported excellent results in new scaffolds with unidirectional interconnection. It has a porosity of 75-84% and a porous network with a diameter of 100-350 µm [46,50].…”
Section: Cell Affinity Of Scaffoldsmentioning
confidence: 99%
“…Porous materials (including ceramic, metallic and polymeric types) are being developed and employed in different fields [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Among these types of porous materials, many researchers are investigating porous ceramics [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%